(untitled) (Belügyi Szemle, 2024)
Aim: The aim of the article is to present the practical aspects of Europol’s role in Hungarian law enforcement. Methodology: We have collected knowledge about the operation of Europol, its services and support of law enforcement by studying the available EU and Hungarian regulations, as well as performing the former management tasks of Europol Hungarian Liaison Bureau, and practical implementation of the tasks of the crime coordinator assisting domestic procedures. Findings: Europol’s law enforcement services provide Hungarian law enforcement agencies with opportunities that cannot be provided by other agencies. In addition to supporting specific investigations, the institutional system also provides IT, strategic and financial support to countries. Value: The study provides operational, practical insights into the possibilities of cooperation with Europol, which will allow the staff of the criminal and judicial authorities to have a deeper insight into the more effective detection and investigation, as well as answers on the individual services and their future, also interpreted in the context of the readers.